Henry White Edgerton papers - Edgerton, Henry White, 1888-1970.
Correspondence, memoranda, writings, reports, notes, case files, newspaper clippings, and other papers relating primarily to White's career as a law professor at Cornell University and judge for the U.S. Court of Appeals (District of Columbia Circuit). Also documents his activities in the Association of American Law Schools. Subjects include civil liberties, criminology, law school curriculum, the U.S. National Recovery Administration, and the roles of the three branches of government. Correspondents include Herschel Whitfield Arant, Felix Frankfurter, Archibald Graustein, Rufus C. Harris, Justin Miller, Roscoe Pound, J.J. Robinson, and John Barker Waite.
Jurist, lawyer, and educator.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection material in English.
Keywords: Arant, Herschel Whitfield, -- 1887- -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Graustein, Archibald -- Correspondence; Harris, Rufus C. -- 1897-1988 -- Correspondence; Miller, Justin, -- 1888-1973 -- Correspondence; Pound, Roscoe, -- 1870-1964 -- Correspondence; Robinson, J. J. -- Correspondence; Waite, John Barker, -- 1882- -- Correspondence; United States. -- Court of Appeals (District of Columbia Circuit); United States. -- National Recovery Administration; Association of American Law Schools; Cornell University; Civil rights; Courts -- Washington (D.C.); Criminology; Law -- Study and teaching; Law -- United States; Separation of powers -- United States; United States -- Politics and government; Educators; Jurists; Lawyers